2020
DOI: 10.3390/ijerph17051522
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Air Pollution on Tuberculosis Based on Kriged Data: A Time-Series Analysis

Abstract: Tuberculosis (TB) has a very high mortality rate worldwide. However, only a few studies have examined the associations between short-term exposure to air pollution and TB incidence. Our objectives were to estimate associations between short-term exposure to air pollutants and TB incidence in Wuhan city, China, during the 2015–2016 period. We applied a generalized additive model to access the short-term association of air pollution with TB. Daily exposure to each air pollutant in Wuhan was determined using ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
(65 reference statements)
1
23
0
Order By: Relevance
“…However, evidence described in the literature confirmed the importance of conducting a study to better understand how air quality and weather can influence the cases of TB. Environmental factors such as air quality index [ 15 ], concentration of carbon monoxide [ 16 ], nitrogen dioxide [ 17 ] and sulphur dioxide [ 18 ], particulate matter [ 19 ] and weather factors such as rainfall [ 20 ], humidity [ 21 ], temperature [ 22 ], wind speed [ 23 ], and atmospheric pressure [ 24 ], can enhance the reproduction and growth of Mycobacterium tuberculosis to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence described in the literature confirmed the importance of conducting a study to better understand how air quality and weather can influence the cases of TB. Environmental factors such as air quality index [ 15 ], concentration of carbon monoxide [ 16 ], nitrogen dioxide [ 17 ] and sulphur dioxide [ 18 ], particulate matter [ 19 ] and weather factors such as rainfall [ 20 ], humidity [ 21 ], temperature [ 22 ], wind speed [ 23 ], and atmospheric pressure [ 24 ], can enhance the reproduction and growth of Mycobacterium tuberculosis to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…The use of statistical models can also be employed to explore potential associations between exposure to air pollutants and health outcomes to highlight potential causal relationships. A study conducted in Wuhan city (China) evaluated the time-series of air pollutants (PM 2.5 , PM 10 , SO 2 , NO 2 , CO and O 3 ) and focused on the tuberculosis’ incidence in order to identify its potential association with short-term exposure to air pollution, based on kriged data and single and multi-pollutant models [ 13 ]. Single pollutant models showed that an increase of 10 μg/m 3 in concentrations of PM 2.5 , PM 10 and O 3 promoted an increase of the associated tuberculosis risk, while in the multi-pollutant model, only PM 2.5 showed a statistically significant effect on tuberculosis incidence.…”
Section: Health Impacts Of Human Exposure To Air Pollutionmentioning
confidence: 99%
“…This allows the estimation of parameters of interest in relatively large geographical regions (Liao, Li & Zhang, 2017), where only a sparse sampling is available (Oliver & Webster, 2014). While interpolation protocols have been developed that improve on Ordinary Kriging, this model is among the most utilized methods in environmental studies, including those considering atmospheric pollution (Liao, Li & Zhang, 2017;Gupta et al, 2018;Gómez-Losada et al, 2019;Huang et al, 2020).…”
Section: Statistical and Spatial Analysesmentioning
confidence: 99%